2023
DOI: 10.1111/aogs.14565
|View full text |Cite
|
Sign up to set email alerts
|

Social egg freezing: Motivations, treatment experiences and the impact of Covid‐19 – a single‐center experience

Abstract: Introduction This study aims to assess the motivations and treatment experiences of women undergoing social egg freezing and to understand the impact of the Covid‐19 pandemic. Material and methods Between January 2011 to December 2021, 191 social egg freezing patients were recruited from the Lister Fertility Clinic, London UK. Participants completed a validated questionnaire investigating patients’ perspectives of social egg freezing. A response rate of 46.6% was achieved. Results In all, 93.9% of women expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Interestingly, in recent years, this practice of sponsored egg freezing has often been used by American companies [59,60]. This raises ethical concerns as women are encouraged to be dedicated and productive at work and, at the same time, they are indirectly obliged to postpone motherhood [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in recent years, this practice of sponsored egg freezing has often been used by American companies [59,60]. This raises ethical concerns as women are encouraged to be dedicated and productive at work and, at the same time, they are indirectly obliged to postpone motherhood [31].…”
Section: Discussionmentioning
confidence: 99%
“…Also, there is a lack of financial programs for reinforcing procreation and raising children at a young age [22]. Some private insurance companies have also started to cover the cost of this procedure [31]. In order for the procedure to be cost-effective, studies showed that 49-61% of patients need to return to use their oocytes, which is very high compared to the current rates [3].…”
Section: Cost Of Proceduresmentioning
confidence: 99%
See 1 more Smart Citation